The Level of Satisfaction of Family Physician Program in Urban Population of Fasa from 2014 to 2015 - Farzaneh Mobasheri; Saeedeh Jafarzadeh; Ehsan Bahramali (Fasa University of Medical Sciences, 2017)
Background & Objective: Patient satisfaction is an indicator of the health services that is increasingly important in today's competitive world and perhaps the simplest method for evaluation of family physician program. This study aimed to determine the level of satisfaction of service recipients in urban areas in Fasa, Iran, with implementation of the Family Physician Program. Materials & Methods: This descriptive cross-sectional study was carried on the 411 patients for whom family physician program was implemented in 2014. Data were collected by a valid and reliable demographic and satisfaction questionnaire in 6 dimensions (care and reverence, trust and belief in his performance, waiting time, availability and timely access to a doctor in time, usefulness of actions, payment costs and paramedical unit performance and on time accessibility, professional services and emergency). Data were analyzed using SPSS software version 18 using independent-samples t-test, chi square test, and ANOVA. Results: Only 1.7% of people had little satisfaction. However, the majority of people expressed consent in all aspects of the Satisfaction of the Family Physician Project. The highest levels of satisfaction were observed in care, respect, trust and belief and the emergency services were observed in the lowest level of satisfaction. Conclusion: Good satisfaction after implementing the family physician program shows the successfulness of the program. Therefore, implementation of family physician program will be a significant milestone for other cities but in order to increase the satisfaction of the emergency services and relevant programs, revision seems necessary in order to improve some of the indices of people satisfaction.